Marketing Training For Grape Plantation Products To Vineyard Entrepreneurs In Bangunsari Village, Tanjung Morawa District, Deli Serdang Regency, Sumatera Utara - Agus Edy Rangkuti; Dina Arfianti Siregar; Muhammad Zuardi; Erwinsyah Simanungkalit; Ahmad Kholil; Siti Raudha Binti Azis; Norshima Binti Sha'ari; Shamariza Binti Maarof (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Bangun Sari Village in Tanjung Morawa District, Deli Serdang Regency, has excellent potential in wine cultivation. However, the business actors still face challenges in product marketing. This training program aims to increase the capacity of vineyard entrepreneurs through training in modern marketing strategies, digital marketing, product packaging, and business institutional formation. The method includes socialization, workshops, direct practice, mentoring, monitoring, and evaluation. The results showed a significant increase in partner skills, the formation of a wine farmer group, and a sales turnover. This activity is expected to be a model for the sustainable development of village-based horticultural agricultural MSMEs.